1990
DOI: 10.1093/jnci/82.13.1127
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Trial of Megestrol Acetate for the Treatment of Cancer Anorexia and Cachexia

Abstract: Preliminary information has suggested that megestrol acetate leads to appetite stimulation and nonfluid weight gain in patients with breast cancer, other cancers, and AIDS. Pursuant to this, we developed a randomized, double-blind, placebo-controlled trial of megestrol acetate in patients with cancer-associated anorexia and cachexia. We randomly assigned 133 eligible patients to receive 800 mg of megestrol acetate per day or a placebo. Patients assigned to megestrol acetate more frequently reported improved ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
1
4

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(133 citation statements)
references
References 0 publications
3
125
1
4
Order By: Relevance
“…They include mainly appetite stimulants and anabolic agents such as prednisolone [15,51] and progesterone [12,42,43,77] and ghrelin, a ligand which stimulates growth hormone release [44,59]. Anecdotally, the use of α-3 omega fatty acids (eicosapentaenoic acid) [52] and thalidomide (potent anti-TNF activity) have been reported [48].…”
Section: Discussionmentioning
confidence: 99%
“…They include mainly appetite stimulants and anabolic agents such as prednisolone [15,51] and progesterone [12,42,43,77] and ghrelin, a ligand which stimulates growth hormone release [44,59]. Anecdotally, the use of α-3 omega fatty acids (eicosapentaenoic acid) [52] and thalidomide (potent anti-TNF activity) have been reported [48].…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials have shown weight increases in patients with cancer-associated cachexia who received megestrol acetate. 24,25 However, body composition studies have shown that the weight gain often is related to gains in adipose tissue and water. 26 In contrast, the weight gains observed in patients with pancreatic carcinoma who were treated with omega-3 fatty acids were associated with improvements in lean body mass.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of dexamethasone in palliative care demonstrated an improvement in anorexia [88]. Megestrol acetate, at varying doses but usually at 800 mg daily, has been shown to stimulate appetite in patients with cancer [62,89]. The adverse events of adrenal insufficiency and venous thromboembolism should be remembered when prescribing megestrol acetate.…”
Section: Gastrointestinal Symptomsmentioning
confidence: 99%